Answer:
1.
-2x - 9y = -3
-7x - 9y= -33
Set equal to y.
-2x - 9y = -3
-9y = 2x - 3
y = -2/9x + 3/9
y = -2/9x + 1/3
-7x - 9y= -33
-9y = 7x - 33
y = -7/9x + 33/9
y = -7/9x + 11/3
Set equal to each other
-2/9x + 1/3 = -7/9x + 11/3
Combine like terms.
5/9x = 10/3
Multiply by 9/5
x = 6
Plug x in.
y = -7/9(6) + 11/3
y = -42/9 + 11/3
y = -42/9 + 33/9
y = -9/9
y = -1
(6, -1)
2.
-3x - 7y = 18
9x + 2y = 3
Set equal to y.
-3x - 7y = 18
-7y = 3x + 18
y = -3/7x - 18/7
9x + 2y = 3
2y = -9x + 3
y = -9/2x + 3/2
Set equal to each other.
-3/7x - 18/7 = -9/2x + 3/2
57/14x = 57/14
Multiply 14/57.
x = 1
Plug x in.
-3(1) - 7y = 18
-3 - 7y = 18
-7y = 21
y = -3
(1, -3)